Pemahaman Peserta Didik SDIT Albanna Dalam Pembelajaran - Nurul Maulida Sofa; Farisa Naeli Setia Aji; Najwa Riska Auliyail Hasanah; Fatin Laelani Putri; Tina Ardianti; Nasokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to observe the level of understanding of students at SDIT Albanna Denpasar in the learning process. As a leading integrated Islamic educational institution in Denpasar City, Bali, SDIT Albanna implements a full-day school system and has begun integrating a bilingual learning program. Data collection was conducted through classroom observation techniques, in-depth interviews with homeroom teachers and students. The results showed that students' understanding was in the very good category for the material taught using the Contextual Teaching and Learning (CTL) approach and active learning methods. The integration of Islamic and scientific values within the integrated curriculum structure helped students absorb the essence of the material more meaningfully. The main obstacles found included varations in student learning speeds (learning gaps) and the challenge of managing children's focus and concentration towards the end of school hours.